The biosocial genome?: Interdisciplinary perspectives on environmental epigenetics, health and society. (20th September 2017) - Müller, Ruth; Hanson, Clare; Hanson, Mark; Penkler, Michael; Samaras, Georgia; Chiapperino, Luca; Dupré, John; Kenney, Martha; Kuzawa, Christopher; Latimer, Joanna; Lloyd, Stephanie; Lunkes, Astrid; et al.
Abstract : Environmental epigenetics has attracted attention in the media owing to its potential for informing public health policies. It is therefore important to take its societal implications into consideration by cooperating with researchers in the social sciences and humanities.